THE USE OF THE SOCIAL NETWORK 'VKONTAKTE' IN UNIVERSITY - Kseniya O. Staroverova (Вестник Российского экономического университета имени Г. В. Плеханова)
Computerization of modern society requires new forms of interaction between the lecturer and the student, including the use of social networks. The article proposes 3 lines in using social networks in the teaching process: for education and methodological support in learning subjects; for consulting graduate-students; for technological support of project work. The author presents advantages of using the social network 'VKontakte' to resolve each of the mentioned above problems and shows possible difficulties connected with this technology and ways of their settlement. As a basis of the research the author uses the results of her work with students of the Russian Plekhanov University of Economics training in specialty 'Customs'.